Challenges in the Handling of Procurement Complaints: Ghana’s Experience - Adjei, A.B. (Journal of Malaysian and Comparative Law, 2011)
Before the coming into force of the current legislative and institutional framework, the laws and institutions regulating public procurement in Ghana were fragmented and uncoordinated. The Public Procurement Act has not only tried to harmonize these laws and procedures, it also created the Public Procurement Authority as a central body responsible for policy formulation and regulation of procurement in Ghana. Considering the historical background and the current state of affairs, there is bright hope for the future. This paper seeks to share with you the experiences of Ghana in the handling of procurement complaints under the Public Procurement Act, 2003 (Act 663). This Act is the primary legislation regulating government contracting in Ghana.